2015
DOI: 10.1002/anie.201504459
|View full text |Cite
|
Sign up to set email alerts
|

A Single Stereodynamic Center Modulates the Rate of Self‐Assembly in a Biomolecular System

Abstract: Chirality is a property of asymmetry important to both physical and abstract systems. Understanding how molecular systems respond to perturbations in their chiral building blocks can provide insight into diverse areas, such as biomolecular self-assembly, protein folding, drug design, materials, and catalysis. Despite the fundamental importance of stereochemical preorganization in nature and designed materials, the ramifications of replacing chiral centers with stereodynamic atomic mimics in the context of biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 106 publications
1
21
1
Order By: Relevance
“…A similar enhancement of cis rotamer population was recently observed for γ-azaproline, while the conformational characteristics of γ-(dimethylsila)­proline closely mimic those of Pro . α-Azaproline, which harbors a stereodynamic α center, was recently accommodated within a well-folded all- trans collagen model system without significant energetic penalty …”
Section: Introductionmentioning
confidence: 86%
“…A similar enhancement of cis rotamer population was recently observed for γ-azaproline, while the conformational characteristics of γ-(dimethylsila)­proline closely mimic those of Pro . α-Azaproline, which harbors a stereodynamic α center, was recently accommodated within a well-folded all- trans collagen model system without significant energetic penalty …”
Section: Introductionmentioning
confidence: 86%
“…17 We posit that the nitrogen atoms in azGly adopt a planar sp 2 -like geometry similar to that of N-amidourea small molecules (see Figures S4−S8), in contrast to the sp 3 -like pyramidal geometry adopted by the nitrogen atoms in some sterically crowded semicarbazides. 12 Out of 11 structures containing the same azGly substructure, average values for ϕ were −112 ± 41°, ranging from −67 to −172°. Average values of ψ were −175 ± 8 and 173 ± 5°, appearing to have amide-like character and an inherent preference for the values needed to mimic collagen Gly residues.…”
mentioning
confidence: 92%
“…10,11 Previous studies in our laboratory have demonstrated several effective modifications to the collagen backbone. 1,2,12,13 Notably, the substitution of glycine with aza-glycine (azGly, azG) was shown to enhance the stability of the collagen triple helix. 1,2 We have since used azGly substitution to stabilize several collagen model peptides (CMPs) made up of POG triplet repeat sequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typical concentrations are 50–500 μM and temperature gradients of 4–12 °C/h. These variations of experimental conditions lead to deviations of up to several degrees centigrade for similar CMPs. ,, NMR spectroscopy exploits the known phenomenon of the high-field shift of Pro Hδ (Xaa position) in the folded triple-helical form (red in Figure ). , …”
mentioning
confidence: 99%